Airborne power ultrasound for drying process intensification at low temperatures: Use of a stepped-grooved plate transducer. Issue 2 (17th March 2021) - Andrés, R. R.; Riera, E.; Gallego-Juárez, J. A.; Mulet, A.; García-Pérez, J. V.; Cárcel, J. A.
Abstract: The recent development of a novel family of power ultrasonic transducers with extensive radiating surfaces represents a step forward in the implementation of new airborne power ultrasonic (APU) technologies for drying process intensification at low temperature. These systems have been successfully used to assist drying of different products at laboratory level. This work deals with the development, integration, and testing of a new APU transducer with a stepped-grooved circular radiator as an initial step in scaling up the process and the results achieved in experiments of airborne atmospheric freeze-drying (AFD) of apples. The results confirm that ultrasound application leads to a significant intensification of the processes. The modeling shows that the increase of kinetic parameters was lower than those obtained with cylindrical transducers having the same electrical input. This fact is attributed to the treatment of greater volume.